"Two Birds with One Stone" Ruthenium(II) Complex Probe for Biothiols Discrimination and Detection In Vitro and In Vivo. Issue 14 (29th May 2020) - Liu, Chaolong; Liu, Jianping; Zhang, Wenzhu; Wang, Yong‐Lei; Liu, Qi; Song, Bo; Yuan, Jingli; Zhang, Run
Abstract: In this work, a "two birds with one stone" ruthenium(II) complex probe, Ru‐NBD, is proposed as an effective tool for biothiols detection and discrimination in vitro and in vivo. Ru‐NBD is nonluminescent due to the quenching of Ru(II) complex emission by photoinduced electron transfer (PET) from Ru(II) center to NBD and the quenching of NBD emission through 4‐substitution with "O" ether bond. Ru‐NBD is capable of reacting with Cys/Hcy to form long‐lived red‐emitting Ru‐OH and short‐lived green‐emitting NBD‐NR, while reacting with GSH to produce Ru‐OH and nonemissive NBD‐SR. The long lifetime emission of Ru(II) complex allows elimination of short lifetime background and NBD‐NR fluorescence for total biothiols detection ("bird" one) by time‐gated luminescence (TGL) analysis, and the remarkable difference in luminescence color response allows discrimination GSH and Cys/Hcy ("bird" two) through steady‐state luminescence analysis. Ru‐NBD features high sensitivity and selectivity, rapid luminescence response, and low cytotoxicity, which enables it to be used as the probe for luminescence and background‐free TGL detection and visualization of biothiols in live cells, zebrafish, and mice. The successful development of this probe is anticipated to contribute to the future biological studies of biothiols roles in various diseases. Abstract : A "two birds with one stone" ruthenium(II) complex probe, Ru‐NBD, is reported for biothiols detection and discrimination in vitro and in vivo. Ru‐NBD ("stone") is capable of detecting total biothiols ("bird" one) by time‐gated luminescence (TGL) analysis and discriminating glutathione and cysteine/homocysteine ("bird" two) through steady‐state luminescence analysis.